Adaptive Renewal of Mountainous Historical Towns Based on the Stability of the Social Network Structure: A Case Study in Chongqing, China - Shi, Yaling; Huang, Yong; Zhang, Ran; Jiang, Di; Zhang, Junxue (Frontiers in Public Health, 2022)
The stability of the social network structure (SSNS) in historical towns is influenced by the changes in the built environment and demographic factors. The historical towns in China have evolved into massive rural-urban migration and the growth of the market-oriented economy under the rapid urbanization over the past forty years. In this context, many of those historical towns experienced ‘declining built environment and disintegrating social networks’, which does not contribute to the adaptive renewal of the built environment and social networks in historical towns, as well as the psychological health of residents. This paper is intended to explore the adaptive renewal of the built environment and social networks of historical towns based on the SSNS. The data of ‘households’ and ‘social ties (i.e., kinship, geographic or job relationship)’ among households were collected via a field survey in seven historical towns in Chongqing, China. The k-core models of the social network analysis (SNA) were calculated to analyse the SSNS. The result shows that social networks of historical towns with centripetal-shaped structures were more stable than that of the historical towns with divergent-shaped structures. Moreover, spatial layout forms and function of households might affect the stability of the social network in historical towns. Based on the analysis results of the SSNS, strategies for the adaptive renewal of the built environment and social networks were put forward on two aspects. The built environment, such as the classification of public spaces and service facilities, can be designed based on the k-core indicator for increasing the spatial connection of households in the historical towns with an incoherent spatial layout form. In addition, increased social activities in the historical towns with a weak SSNS may promote the social connection of households, which are also helpful to boost the public health at psychological aspects.